2016
DOI: 10.1080/1343943x.2016.1221320
|View full text |Cite
|
Sign up to set email alerts
|

Suppression subtractive hybridization library construction and identification of epidermal bladder cell related genes in the common ice plant, Mesembryanthemum crystallinum L.

Abstract: Mesembryanthemum crystallinum L., a halophytic species, displays modified trichomes, epidermal bladder cells (EBC), on the surfaces of its aerial organs. EBCs serve to sequester excessive salt from underlying metabolically active tissues. To elucidate the molecular determinants governing EBC development in the common ice plant, we constructed a cDNA-based suppression subtractive hybridization library and identified genes differentially expressed between the wild-type and the EBC-less mutant. After hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Some of the lineage specific transcripts are easily detected in the epidermal bladder cell transcriptomes at high expression levels, but appear to be expressed at low levels or are undetected in whole shoot transcriptomes, indicating the importance of studies of individual salt gland cell types (Oh et al, 2015). Genes specific to bladder cell function and development that were identified using a suppression subtractive hybridization library construction between wild type M. crystallinum and mutant plants without bladder cells also revealed a significant number of lineage specific genes with unknown functions (Roeurn et al, 2016). One such gene of unknown function detected via the comparison between wildtype and mutant plants was subsequently overexpressed in Arabidopsis , resulting in a phenotype with an increased number of trichomes on leaves, and this gene was inferred to regulate trichome initiation via regulating GL2 in the trichome development pathway (Roeurn et al, 2016).…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
“…Some of the lineage specific transcripts are easily detected in the epidermal bladder cell transcriptomes at high expression levels, but appear to be expressed at low levels or are undetected in whole shoot transcriptomes, indicating the importance of studies of individual salt gland cell types (Oh et al, 2015). Genes specific to bladder cell function and development that were identified using a suppression subtractive hybridization library construction between wild type M. crystallinum and mutant plants without bladder cells also revealed a significant number of lineage specific genes with unknown functions (Roeurn et al, 2016). One such gene of unknown function detected via the comparison between wildtype and mutant plants was subsequently overexpressed in Arabidopsis , resulting in a phenotype with an increased number of trichomes on leaves, and this gene was inferred to regulate trichome initiation via regulating GL2 in the trichome development pathway (Roeurn et al, 2016).…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
“…The increased expression of McMYB2 resulted in the increased number of trichomes in the transgenic Arabidopsis (Figure 4). In Arabidopsis, it has been suggested that R2R3 MYBs (GL1, MYB5, and MYB23) interact with a bHLH protein (GL3 and that WM28 positively regulated trichome in Arabidopsis by increase of the expression of genes for trichome development-acting complex, GL1 and GL3 (Roeurn et al, 2016). In the present study, we attempt to further elucidate the molecular genetic basis of the development of EBCs in the common ice plant through the analysis of the common ice plant homologs of the trichome and fiber-development related-genes of Arabidopsis and cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Development of cotton fibers takes place from 0 to 60 d post-anthesis (DPA) that including fiber initiation, elongation, biosynthesis of secondary cell walls, and maturation (Lee et al, 2007;Li et al, 2002). Genes for several transcription factors that function in fiber development, including GaMYB2, GhMYB25, GhMYB109, and a putative homeodomain transcription factor GhHD1, which are preferentially expressed in early fiber initiation, have been identified (Suo et al, Wild type of Arabidopsis thaliana (ecotype Col-0) and the gl2-1 mutant in Landsberg erecta (Koornneeff et al, 1982) were obtained from the Arabidopsis Biological Resource Center and were cultured as described previously (Roeurn et al, 2016). The seeds were surfaced sterilized and sown on 1/2 MS basal medium with Gamborg's vitamins and 10 g L −1 sucrose (0.8% agar), and were vernalized at 4 °C for 2-3 d before germinating at 22 °C under constant light with a light intensity of ca.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations